Estrategias de enseñanza en el aprendizaje de la educación física en estudiantes de educación secundaria de la Institución Educativa N° 60014 Santo Cristo de Bagazán, Belén 2023 - Concha Calampa, Paola (2025)
The present research aims to understand how teaching strategies improve learning in secondary education students at Educational Institution No. 60014 Santo Cristo de Bagazán, Belén 2023. In this regard, it was guided by a quantitative approach, with a descriptive and correlational type and design. The focus was on working with a student population of 114 learners, with a margin of error of 8%; two checklists were used as instruments, where the results showed that students improve their learning by correctly using teaching strategies. It can also be demonstrated that at the secondary level, the learning strategy that yields the best results is teamwork, as it allows for the strengthening of knowledge in a group manner and also builds knowledge with the contributions of each participant. In the data analysis through the non-parametric Spearman's Rho test, which yielded a positive valuation coefficient of 0.372, with a p<.001, we affirm that there is a significant relationship between the research variables. Therefore, the implementation of teaching strategies contributes to the strengthening of learning in secondary level students.